How to Control Coastal Zone Through Spatial Planning? Taking the Construction of the Spatial Monitoring Index System of the Coastal Zone in China as an Example - Guo, Zelian; Hu, Yecui; Bai, Yuping; Yang, Lei; Wang, Jieyong (Frontiers in Environmental Science, 2022)
Due to its fragile ecological environment, superior natural and location conditions, coastal areas are receiving extensive attention all over the world. Scientific space control is needed to ensure the harmonious development of the "Human-land-ocean" system in this region. The monitoring index system is a crucial grasp of the national territory use control; it is also one of the main contents in the reform of China's planning system in the new era. Therefore, based on the strategic idea of land-sea overall management and the concept of "life community of human, mountains, rivers, forests, farmlands, lakes, grasslands and ocean", this paper puts forward three connotations of the index system of coastal spatial planning from the perspective of "function-structure-elements". Then, adopt the methods of "multiple planning integration" and expert consultation, and using the research idea of "setting control objectives, contents and indicators", an index system suitable for coastal space control is constructed. The results show that the index system puts forward 33 sub-indexes for coastal ecological space, living space and production space, and provides a basis for the high-quality development of coastal space through the restrictions and requirements on the total amount, bottom line, boundary, conversion and quality of various spatial elements. This study can provide a basis for the formulation, implementation and later monitoring of coastal spatial planning, and provide an index reference for the management of coastal areas in other countries in the world.